Biocatalysts and enzyme technology - Buchholz, Klaus, 1941-; Kasche, Volker; Bornscheuer, U. T. (Uwe Theo), 1964- (Weinheim : Wiley-VCH, 2005)
"An instructive and comprehensive overview of our current knowledge of biocatalysis and enzyme technology. Following an introduction to the history of enzyme applications and the motivations for using these highly selective and environmentally friendly methods, the book goes on to cover enzyme mechanisms and kinetics, production, recovery, characterization and their design, including recombinant methods. Alongside the application of soluble and immobilized biocatalysts, including whole-cell systems, the authors treat the use of non-aqueous reaction systems, applications in organic synthesis, bioreactor design and reaction engineering. A number of case studies further exemplify the advantages of enzyme processes. Each topic includes exercises, designed to facilitate access to this flourishing area of research."--BOOK JACKET.
1. Introduction to enzyme technology -- 2. Basics of enzymes as biocatalysts -- 3. Enzymes in organic chemistry -- 4. Enzyme production and purification -- 5. Application of enzymes in solution : soluble enzymes and enzyme systems -- 6. Immobilization of enzymes (including applications) -- 7. Immobilization of microorganisms and cells -- 8. Characterization of immobilized biocatalysts -- 9. Reactors and process technology -- App. I. The world of biotechnology information : eight points for reflecting on your information behavior.
Includes bibliographical references and index.
All Ages.
Keywords: Enzymes -- Industrial applications; Enzymes -- Biotechnology; Catalysis; Enzymes; Biotechnology